Compliance with Personal Protective Equipment Use Among Chemistry Laboratory Students: The Role of Knowledge, Attitude, and Availability of Facilities - Izzuddin, M.; Sari, Yusnita; Imanuddin, M. Rizki (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
Compliance with personal protective equipment (PPE) usage is an important indicator of occupational safety implementation in chemistry laboratories, which carry high risks of accidents and hazardous material exposure. This study aimed to analyze the relationship between knowledge, attitude, and PPE availability with compliance among students of the Environmental Health Department at Poltekkes Kemenkes Banjarmasin. A cross-sectional study design with a quantitative approach was employed. The study sample consisted of 80 students, including 40 students from the Diploma Three Program, 4th semester, and 40 students from the Applied Bachelor Program, 6th semester, selected using total sampling. Data were collected through direct observation and structured questionnaires, then analyzed using the Chi-square test at a 0.05 significance level. The results showed that knowledge (p=0.539) and attitude (p=1.000) were not significantly associated with PPE compliance. PPE availability also did not show a significant relationship (p=0.164); however, there was a tendency for higher compliance when PPE was adequately available (65.7%) compared to insufficient availability (40.0%). These findings align with the PRECEDE–PROCEED model, which emphasizes the role of enabling factors in shaping health behaviors. The results highlight that improving compliance cannot rely solely on education and positive attitude formation but also requires adequate PPE provision, continuous supervision, and the establishment of a safety culture in the educational environment.